REAL EARNINGS MANAGEMENT AND CASH HOLDING PERFORMANCE: AUDITOR INDUSTRY SPECIALIZATION AS MODERATING VARIABLE - Mukhlasin, Mukhlasin (JRAK, 2024)
This academic work intends to obtain empirical evidence about the signaling perspective on real earnings management to describe cash holdings. The theoretical contradictions of real earnings management reflect management's opportunistic attitude and optimistic attitude which signifies positive earnings. The research design is a quantitative study with a sample of 216 units of analysis. Secondary research data was obtained from the Indonesian stock exchange for 2019-2021. Multiple linear regression testing results prove that real earnings management gives a positive signal about cash holding. Auditor industry specialization which reflects audit quality is proven to strengthen the relationship between real earnings management and cash holding. This contributes to the realm of signal theory as an alternative explanation of the relationship between real earnings management and cash holding. In addition, the role of industry-specialized auditors is a driving force in strengthening positive signals that reflect alignment between management policies and cash-holding performance.